2013
DOI: 10.1590/0004-282x20130026
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and laboratorial characterization and post-surgical follow-up of 87 patients with non-functioning pituitary macroadenomas

Abstract: Objective:It was to assess the main characteristics of patients undergoing pituitary tumor surgery.Method:Eighty-seven patients (44 men; 44.8±13 years old) were included.Results:The main symptoms were visual alterations (87.3%), headache (70.1%), diminished libido (34.4%), galactorrhea (22.9%) and hair loss (19.5%). The axes affected were gonadotropic (72.6%), thyrotropic (48.4%) and corticotropic (38.7%), without significant changes after surgery. The average largest tumor diameter was 3.1 cm before surgery a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
13
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 21 publications
4
13
0
3
Order By: Relevance
“…The development of other major complications viz. CSF leak (10%), nasal bleeding (5·7%), meningitis (4·3%), cranial nerve palsies (4·3%) and hemiplegia (2·9%) is also comparable with rates from other centres; however, in a report on 570 patients with NFPA by Berker et al ., the overall complication rate was 12·1%, with low rates of postoperative CSF leak (0·8%), meningitis (0·8%), permanent DI (0·4%) and no deaths. We found a higher rate of postoperative hydrocephalus (7·1%) than that reported by others (1·4–6%) .…”
Section: Discussionsupporting
confidence: 71%
See 4 more Smart Citations
“…The development of other major complications viz. CSF leak (10%), nasal bleeding (5·7%), meningitis (4·3%), cranial nerve palsies (4·3%) and hemiplegia (2·9%) is also comparable with rates from other centres; however, in a report on 570 patients with NFPA by Berker et al ., the overall complication rate was 12·1%, with low rates of postoperative CSF leak (0·8%), meningitis (0·8%), permanent DI (0·4%) and no deaths. We found a higher rate of postoperative hydrocephalus (7·1%) than that reported by others (1·4–6%) .…”
Section: Discussionsupporting
confidence: 71%
“…In our study, adjunctive radiotherapy was used in 18Á6% of patients, due to persistence of a large residual tumour following surgery. Gondim et al 19 reported the use of adjuvant radiotherapy in only 6%, and in the study by de Mello et al, 5 radiotherapy was used in 27% of the 87 patients with NFPA.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations